PENERAPAN ASESMEN FORMATIF DIGITAL BERBASIS GAMIFIKASI ZEP QUIZ PADA MATERI LITERASI FINANSIAL KELAS IX SMPN 1 CILIMUS - Anggun Gumilar; Dina Siti Logayah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Conventional classroom practices require the use of digital, gamified assessment tools such as Zep Quiz to enhance students’ motivation and the accuracy of learning evaluation. This study focuses on examining the effectiveness of the Zep Quiz digital assessment in improving students’ motivation and the quality of evaluation in financial literacy learning. This research employed a qualitative method with a case study design through observations, interviews, documentation, interactive data analysis, and three procedural stages: preparation, implementation, and reporting. The findings indicate that formative assessment supported by gamification through Zep Quiz increases students’ engagement, motivation, and the quality of feedback in financial literacy learning at SMPN 1 Cilimus. Students actively participated in the assessment, understood their errors more quickly through instant feedback, and showed strong enthusiasm due to game elements such as points and leaderboards. Teachers obtained real-time learning achievement data that enabled them to adjust instruction based on students’ needs. From a gamification perspective, Zep Quiz stimulates both intrinsic and extrinsic motivation through challenges, competition, and digital rewards. Using Rogers’ diffusion of innovation framework, the adoption process of Zep Quiz is reflected in the stages of knowledge, persuasion, decision, implementation, and confirmation experienced by teachers and students. Nevertheless, the study also identifies challenges related to network stability, technical readiness, and students’ varying digital abilities. Overall, Zep Quiz is considered effective as an engaging, adaptive, and relevant formative digital assessment tool for enhancing students’ financial literacy understanding in social studies learning ABSTRAKPembelajaran yang masih konvensional menuntut adanya asesmen digital berbasis gamifikasi seperti Zep Quiz untuk meningkatkan motivasi dan akurasi evaluasi belajar siswa. Penelitian ini berfokus pada efektivitas asesmen digital Zep Quiz dalam meningkatkan motivasi dan kualitas evaluasi literasi finansial. Metode yang digunakan adalah kualitatif dengan desain studi kasus melalui observasi, wawancara, dokumentasi, analisis data interaktif, serta prosedur penelitian tiga tahap, yaitu persiapan, pelaksanaan, dan pelaporan. Hasil penelitian menunjukkan bahwa asesmen formatif berbasis gamifikasi melalui Zep Quiz mampu meningkatkan keterlibatan, motivasi, dan kualitas umpan balik dalam pembelajaran literasi finansial di SMPN 1 Cilimus. Siswa terlihat lebih aktif mengikuti asesmen, lebih cepat memahami kesalahan melalui umpan balik instan, serta menunjukkan antusiasme tinggi berkat elemen permainan seperti poin dan leaderboard. Guru memperoleh data capaian belajar secara real time sehingga dapat menyesuaikan pembelajaran sesuai kebutuhan siswa. Dari perspektif gamifikasi, Zep Quiz memicu motivasi intrinsik dan ekstrinsik melalui tantangan, kompetisi, dan reward digital. Melalui kerangka difusi inovasi Rogers, proses adopsi Zep Quiz terlihat melalui tahapan pengetahuan, persuasi, keputusan, implementasi, dan konfirmasi yang dilalui guru dan siswa. Kendati demikian, penelitian juga menemukan kendala seperti keterbatasan jaringan, kesiapan teknis, dan variasi kemampuan digital siswa. Secara keseluruhan, Zep Quiz efektif sebagai asesmen formatif digital yang menarik, adaptif, dan relevan untuk meningkatkan pemahaman literasi finansial dalam pembelajaran IPS.